2022
DOI: 10.9734/arjom/2022/v18i730391
|View full text |Cite
|
Sign up to set email alerts
|

Application of Stacking-Based Ensemble Learning Model for Water Quality Prediction

Abstract: Water is the source of life, and the growth of animals and plants cannot leave the water source. The quality of water will directly affect the life and health of humans, animals and plants. In order to predict the concentration and changing trend of various pollutants in water bodies and promote the comprehensive management of water resources, this paper proposes a new integrated model based on the idea of Stacking integrated learning. The model is based on XGBoost, support vector regression, and multi-layer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…This study found that the ELM can integrate learning based on the output results of the base model as the input features of the second-layer meta-learner (LR) model, thus better integrating the advantages of the base model and producing more stable results. Meanwhile, different base models were 5-fold cross-validated, avoiding the problem of the poor generalization ability of test data division, effectively suppressing model over-fitting and improving the generalization ability and forecast accuracy of the ELM, similar to the findings of Cui et [20,50,51]. The XGBoost model, as a single machine learning algorithm, was better in forecasting albacore fishing grounds (ACC = 82.53%), where its overall accuracy was 1.58~15.09% better than that of other machine learning algorithms, and its accuracy (R 2 ) in forecasting high-yield tuna fishing grounds reached 90.37%.…”
Section: Discussionmentioning
confidence: 57%
“…This study found that the ELM can integrate learning based on the output results of the base model as the input features of the second-layer meta-learner (LR) model, thus better integrating the advantages of the base model and producing more stable results. Meanwhile, different base models were 5-fold cross-validated, avoiding the problem of the poor generalization ability of test data division, effectively suppressing model over-fitting and improving the generalization ability and forecast accuracy of the ELM, similar to the findings of Cui et [20,50,51]. The XGBoost model, as a single machine learning algorithm, was better in forecasting albacore fishing grounds (ACC = 82.53%), where its overall accuracy was 1.58~15.09% better than that of other machine learning algorithms, and its accuracy (R 2 ) in forecasting high-yield tuna fishing grounds reached 90.37%.…”
Section: Discussionmentioning
confidence: 57%